Analisis Efisiensi Biaya Produksi Secara Syariah Dalam Perkembangan Laba Usaha pada Roti Bakar Regar - Muhammad Hisyam; Ismi Affandi; Anriza Witi Nasution (UIN AM. Sangadji Ambon, 2025)
This study aims to analyze the determinants of production costs and assess the efficiency of sharia-compliant production costs in relation to the growth of business profits at Regar Baked Bread MSMEs. This study adopts a qualitative methodology, employing interviews and documentation methods to examine financial data from December 2024 to May 2025. The results demonstrate that the production costs for this MSME consist of raw materials, labor, and overhead expenses. Efficiency is achieved through cost management and waste prevention, in accordance with Islamic principles. Sharia-compliant practices have been shown to improve the stability and growth of business profits, as well as yield positive results for business operations.